Transcatheter aortic valve implantation for severe aortic regurgitation in a patient with end-stage respiratory failure - Aleksandra Cherneva; Zoran Stankov; Naidenka Zlatareva; Iveta Tasheva; Georgi Dobrev; Galina Georgieva; Ivo Petrov (Българска кардиология, 2020)
We report a case of a high-risk 73-year–old patient with a combined aortic valve disease with predominant severe, symptomatic aortic regurgitation and a history of an end-stage respiratory failure with prohibitive surgical risk who was successfully treated using a minimalist approach to implant off-label а self-expandable Medtronic Evolut R prosthesis. This case report demonstrates that the self-expandable prosthesis Medtronic Evolut R might be implanted without tissue damage and migration in a moderate-calcified tricuspid aortic valve with predominant regurgitation and mild stenosis with satisfactory hemodynamic results and improvement in functional class heart failure in a patient with concomitant severe respiratory failure.